Evaluating the operational suitability to use biometric face recogntion for Kuala Lumpur International Airport (KLIA) immigration / Suhaimi @ Ramdzan Sulaiman - Sulaiman, Suhaimi @ Ramdzan (2007)
Over the pass few decades, people have been travelling around the world to enter a country from one to another. Due to the increasing number of frequent travellers, airport immigration have becomes one of the busiest place on earth for this migration of peoples, entrance check point have to be enlarged, dedicated system have to be set in many location to cater the need for clearance process, security concern based on travel documents and identity fraud has increase over a number of years raising the international alert on the security of the immigration checkpoints. Technology concern on the method to recognize individual based on their unique physical characteristic such as fingerprints, facial, iris, voice has become and alternative means to identify the identity of the travellers. Biometric face recognition for passport identification and verification has been used in many airports around the world to replace the traditional methods for passport identification and verification. KLIA is one of the first airports in the world to introduce the use of a smart passport for domestic clearance process. Traditional methods for clearance process are still used for the international clearance. This study is to find the suitability of biometric face recognition to aid KLIA immigration in the clearance process for international travellers. The suitability is focussed on the evaluation of time and accuracy performance of current face recognition methods comparing with the performance of biometric face recognition methods while evaluating effectiveness- and attitudes towards current clearance and face recognition methods from travellers (foreigners) and officer's point of view. From the analysis, comparing the result for overall average processing time for both, manual and biometric system, indicate that current face recognition could not out perform biometric face recognition. Based on result also we conclude that there is a lot more improvement that could be done to increase the performance of KLIA immigration checkpoint.